PENGARUH PRINSIP-PRINSIP GOOD GOVERNANCETERHADAP KINERJA PEMERINTAH DAERAH PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN MUSI RAWAS - Sunardi Sunardi; Darma Yanti; Wendi Ariansyah (AKUNTABILITAS, 2019)
The formulation of the problem in this study is how the influence of the principles of good governance on the performance of local governments. The purpose of this study is to measure the effect of the principles of good governance on the performance of local governments in the Musi Rawas District Tax and Retribution Management Agency. This research is an associative type of research. The data used in this study are primary data. This study uses a sample, the sample used by 34 respondents. Analysis of the data used in this research is qualitative analysis and quantitative analysis. The results of this study indicate that the principles of good governance significantly have a positive effect on the performance of local governments in the Musi Rawas District Tax and Retribution Management Agency.